An Active Learning Exercise for Product Design from an Operations Perspective. (July 2016) - Hill, Stephen; Baker, Elizabeth
ABSTRACT: Product design is a topic that is regularly covered in introductory operations management courses. However, a pedagogical challenge exists related to the presentation of introductory‐level product design in a way that promotes active learning. The hands‐on exercise presented in this article provides instructors with an activity that gives students an open‐ended opportunity to quickly develop a realistic product from conception to prototype. A unique material is used that allows students the flexibility to freely form a product prototype. A description of the exercise and an assessment of its efficacy in promoting student understanding of product design from an operations perspective are presented. Opportunities for future work are also identified.